Development of a German reading span test with dual task design for application in cognitive hearing research. (February 2015) - Carroll, Rebecca; Meis, Markus; Schulte, Michael; Vormann, Matthias; Kießling, Jürgen; Meister, Hartmut
Abstract Objective: To report the development of a standardized German version of a reading span test (RST) with a dual task design. Special attention was paid to psycholinguistic control of the test items and time-sensitive scoring. We aim to establish our RST version to use for determining an individual's working memory in the framework of hearing research in German contexts. Design: RST stimuli were controlled and pretested for psycholinguistic factors. The RST task was to read sentences, quickly determine their plausibility, and later recall certain words to determine a listener's individual reading span. RST results were correlated with outcomes of additional sentence-in-noise tests measured in an aided and an unaided listening condition, each at two reception thresholds. Study sample: Item plausibility was pre-determined by 28 native German participants. An additional 62 listeners (45–86 years, M = 69.8) with mild-to-moderate hearing loss were tested for speech intelligibility and reading span in a multicenter study. Results: The reading span test significantly correlated with speech intelligibility at both speech reception thresholds in the aided listening condition. Conclusion: Our German RST is standardized with respect to psycholinguistic construction principles of the stimuli, and is a cognitive correlate of intelligibility in a German matrix speech-in-noise test.